The Effect of Pilot Reaction Time and Line-Up Time on Runway Occupancy Time Take-Off about Runway Capacity (Case Study: Soekarno-Hatta International Airport) - Indrawan, Mohammad Ardiansyah Putra; Rosmayanti, Lina; Abimanyu, Yudha (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
One way to increase runway capacity is to set the Runway Occupancy Time Take-Off (ROTT) standard. Following the Aeronautical Information Publication of Soekarno-Hatta International Airport, the ROTT standard is set at 90 seconds. However, many aircraft have a ROTT of more than the standard. This can cause a decrease in the optimal level of runway capacity utilization. It is suspected that factors affect ROTT, namely Pilot Reaction Time and Line-Up Time. This study aims to analyze the effect of Pilot Reaction Time and Line-Up Time on ROTT at Soekarno-Hatta International Airport. The population used is aircraft taking off from Soekarno-Hatta International Airport, with the sample being aircraft taking off in peak seasons. The research method uses Quantitative Methods with observation data collection techniques using the Doratask Method. The data was processed using Non-Parametric Statistics using the Spearman Rank Correlation Method. The results of this study indicate that pilot reaction time has no significant effect on ROTT. However, pilot reaction time has a significant positive and strong relationship with ROTT. Line-up time significantly influences ROTT with a positive and very strong relationship. Pilot reaction time and line-up time simultaneously significantly influence ROTT with a positive and very strong relationship. Pilot reaction time and line-up time have a significant positive relationship.